Presensi Guru dan Karyawan Berbasis LBS dan Face Recognition pada TK Bruder Melati Pontianak - Devi, Cresensia (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study aims to design an Android-based attendance application using Location Based Service (LBS) and Face Recognition technology at TK Bruder Melati Pontianak. The application is designed to address the inefficiencies and errors of the manual attendance system. The system consists of two platforms: a desktop-based application managed by the admin and principal, and an Android-based application used by teachers and staff. LBS technology ensures that attendance can only be recorded within the school area, while Face Recognition validates user identity. Attendance data is automatically stored in the database, and reports can be accessed in real-time. The results show that this application improves the efficiency of the attendance process, data security, and ease of reporting. Further development is suggested to add an authorization feature for leave requests to enhance the system's functionality.